When the money stops: fluctuations in financial remittances and incumbent approval in Central Eastern Europe, the Caucasus and Central Asia - Tertytchnaya, K; De Vries, C; Solaz, H; Doyle, D (Cambridge University Press, 2018)
Fluctuations in the volume and the value of financial remittances received from abroad affect the livelihood of households in developing economies across the world. Yet, political scientists have little to say about how changes in remittances, as opposed to the receipt of remittance payments alone, affect recipients’ political attitudes. Relying on a unique four-wave panel study of Kyrgyz citizens between 2010–2013 and a cross-sectional sample of 28 countries in Central Eastern Europe, the Caucasus and Central Asia, we show that when people experience a decrease (increase) in remittances, they become less (more) satisfied about their household economic situation and misattribute responsibility to the incumbent at home. Our findings advance the literature on the political consequences of remittance payments and suggest that far from exclusively being an international risk-sharing mechanism for developing countries, remittances can also drive fluctuations in incumbent approval and compromise rudimentary accountability mechanisms in the developing world.